Artificial intelligence as a co-author? Rethinking authorship in the context of human interaction with AI - Natalia A. Maslenkova; Anna S. Nikitina (Семиотические исследования)
The increasing integration of artificial intelligence (AI) into the domain of text production challenges the traditional boundaries of authorship. This paper examines whether AI systems can be considered co-authors of texts created in collaboration with humans. We explore this question from cultural, ethical, and philosophical perspectives, drawing on current frameworks in copyright law, literary theory, and digital humanities. The study employs an interdisciplinary methodology, analyzing selected cases of AI-assisted textual production across academic, artistic, and journalistic domains. Particular attention is given to the extent of AI’s semantic contribution and the human agent’s role in directing, editing, or curating the outcome. While current legal systems attribute authorship solely to human individuals, the increasing sophistication of AI tools necessitates re-examining this paradigm. Key issues addressed include the legal non-personhood of AI, the difficulty of attributing creative intent, and the implications of AI-generated content for intellectual property frameworks. We discuss models such as extended authorship, distributed creativity, and networked authorship, suggesting that these may better reflect the hybrid nature of human–AI interaction. We conclude by recommending a context-sensitive, field-specific approach to authorship in AI-mediated creativity. A dialogic framework involving legal scholars, content creators, ethicists, and developers is proposed to develop adaptive guidelines that balance innovation and intellectual responsibility.